Management of Maxillary Incisors With Middle-Third Root Perforation: A Case Report - Daysi Morocho-Monteros; María José Masson-Palacios; Juan Marcos Parise-Vasco (Hindawi Limited, 2024)
Root canal perforations are frequent but critical complications in endodontic treatments, which can pose a risk of irreversible damage to the affected tooth. These perforations typically occur during root canal preparation or endodontic post placement, presenting significant therapeutic challenges. The main objective in the management of such complications is to seal the perforation, thus preventing bacterial invasion and tooth loss. This report details the case of a 70-year-old patient with a perforation in the palatal wall of the middle root section of tooth #11. The treatment approach involved magnification techniques and the application of a bioactive material known as Biodentine. This case underscores the critical role of accurate radiographic evaluation and the use of biocompatible materials in the management of root perforations. Despite inherent challenges, proper diagnosis and planning, combined with appropriate techniques and materials, can lead to satisfactory results, effectively preserving the structure of the tooth.